Could you teach new tricks to old dogs? An analysis of online communication of political leaders in Spanish regional elections - Pérez-Castaños, Sergio; Antón-Merino, Javier; García-Hípola, Giselle (Frontiers in Political Science, 2024)
Two regional elections were held in 2022, marking the start of a new electoral phase in Spain. The first election was held in February in Castilla y León, where the right-wing VOX party formed a coalition government with the right-wing Partido Popular for the first time. At the same time, the far-left party Podemos saw its parliamentary representation significantly reduced. Subsequently, in June, Andalusia held its elections, in which VOX increased its representation by two seats, marking the beginning of its rise at the national electoral level. Conversely, the extreme left, split between two parties, saw its representation decline, losing 10 seats. This study attempts to juxtapose the electoral strategies employed by the leaders of the different political parties, with a particular focus on the communication strategies of leaders and parties on X (formerly Twitter) throughout the campaign period. It is expected that discrepancies will emerge not only between political entities, but also between regions. To investigate this hypothesis, we conducted a content analysis of X accounts, selecting those associated with regional presidential candidates within each region. We distinguish between those considered ‘traditional’ political parties and those considered ‘new’, including in these two categories the main contending political parties in each region. Thanks to the analysis, the proposed objective is achieved, demonstrating the existing differences between the two types of political parties and how their leaders use the social platform X. The results show that all the elements considered in the study are present, although not uniformly across both regions analyzed. This suggests a progressive alignment between new and traditional parties, reflecting a convergence in their strategies for conducting electoral campaigns.